Пірогенний кремнезем з прищепленими кремнієгідридними групами як редокс-активний компонент у складі композита з кавовою кислотою - Кузема, П.О.; Лагута, І.В.; Ставинська, О.М.; Циба, М.М.; Тьортих, В.А. (Доповіді НАН України, 2020)
Шляхом сорбційного модифікування вихідного пірогенного кремнезему (ПК) та гідридсилільованого кремнезему (ГПК) кавовою кислотою (КК) було одержано композити з відновлювальними властивостями (ПК-КК і ГПК-КК відповідно). Результати ІЧ спектральних досліджень показали, що гідроксильні групи поверхні кремнеземів беруть участь в утворенні водневих зв'язків з молекулами КК. Аналіз редокс-активності матеріалів виявив значне зниження окисно-відновного потенціалу водної системи зразками на основі ГПК. За допомогою ДФПГ-тесту встановлено відсутність антирадикальних властивостей у ПК та ГПК, проте композити ПК-КК і ГПК-КК, як і КК, ефективно нейтралізують радикали дифенілпікрилгідразилу. За допомогою методу Фоліна—Чокальтеу показано, що КК у складі композитів з кремнеземом зберігає свої антиоксидантні властивості. Результати дослідження свідчать про перспективність використання гідрид силільованого пірогенного кремнезему як редокс-активного компонента у складі композитів антиоксидантної дії. Using the sorptive modification of pristine fumed silica (FS) and hydride-silylated silica (HFS) with caffeic acid (CA), the composites with reducing properties (FS-CA and HFS-CA, respectively) were obtained. Based on the results of IR spectrometry, it was concluded that, under such conditions of deposition, caffeic acid at a concentration of 24 mg per g of silica is rather in the adsorbed state than in the condensed one, the surface hydroxyl groups of both unmodified and hydride-silylated fumed silica being involved in the interaction with the carbonyl and probably phenolic groups of CA molecules, whereas grafted silicon-hydride groups do not participate in the formation of surface complexes with this antioxidant. Reducing properties of the materials in aqueous medium were estimated by a change in the oxidation-reduction potential (ORP) and the complex index of redox activity (rH2) taking into account pH with respect to distilled water. The measurements have shown that only HFS and HFS-CA are capable of lowering the ORP of aqueous medium. Moreover, HFS-CA has shown the most attractive results in terms of both the values of the redox activity in the aqueous medium and their stability over time. DPPH test showed that FS and HFS possess no antiradical properties. However, it was found that FS-CA and HFS-CA composites, as well as CA, effectively neutralize diphenylpicrylhydrazyl radicals. Using the Folin–Ciocalteu method, it has been shown that CA in the composition with silica preserves its antioxidant properties. The studies have shown a promise of using hydride-silylated fumed silica as a redoxactive component for antioxidant composites. Путем сорбционного модифицирования исходного пирогенного кремнезема (ПК) и гидридсилилированного кремнезема (ГПК) кофейной кислотой (КК) были получены композиты с восстановительными свойствами (ПК-КК и ГПК-КК соответственно). Результаты ИК спектральных исследований показали, что гидроксильные группы поверхности кремнеземов принимают участие в образовании водородных связей с молекулами КК. При анализе редокс-активности материалов обнаружено значительное понижение окислительно-восстановительного потенциала водной системы образцами на основе ГПК. С помощью ДФПГ-теста установлено отсутствие антирадикальных свойств у ПК и ГПК, однако композиты ПК-КК и ГПК-КК, как и КК, эффективно нейтрализуют радикалы дифенилпикрилгидразила. С помощью метода Фолина–Чокальтеу показано, что КК в составе композитов с кремнеземом сохраняет свои антиоксидантные свойства. Результаты исследования свидетельствуют о перспективности использования гидридсилилированного пирогенного кремнезема в качестве редокс-активного компонента в составе композитов антиоксидантного действия.